Management of Continuous Professional Development through Competency-Based Training Model for Junior High School Teachers - . Sherly; Syawal Gultom; Eka Daryanto; . Nasrun (Emerging Science Journal, 2023)
One of the strategies to improve teachers' skills and professionalism is the practice of continuous professional development. To fulfill the demands of students and learning in the 21st century, teachers must have a strong foundation and knowledge of ongoing professional development. However, a-business-as-usual continuous professional development does not contribute to any significant improvements for teachers of junior high school in Pematangsiantar. The objective of this research was to develop a management model for teachers’ continuous development. This is carried out through competency-based training with a heutagogy approach. A development model called ADDIE, which stands for Analysis, Design, Develop, Implementation, and Evaluation was used to develop the management model. The subject of this research was 80 junior high school students in Pematangsiantar. They were divided into 30 and 50 people for the limited trial and the broad trial, respectively. Questionnaires were distributed as the instrument of data collection. The data was then analyzed using a statistical descriptive analysis technique. The research found that the effectiveness of the competency-based training management model was measured by the N-Gain score, in which the G-value was 0.79 and 0.82 for limited trial and broad trial, respectively, which was in the high category. The results of the assessment of the effectiveness of the model obtained an average value of 94%, which was in the "very good" category. The effectiveness of the training program was assessed from the aspects of reactions, learning, behavior, and results, and the results show that the assessment of the classroom action research training program obtained an average score of 92%, or a very good category, which means that the classroom action research training program is very effective in improving teachers’ competence. The significance of this model has been proven to give an innovative solution to teachers’ continuous professional development. Doi: 10.28991/ESJ-2023-07-01-014 Full Text: PDF